PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ANDROID MENGGUNAKAN ISPRING MATERI MICROSOFT WORD KELAS VIII DI SMP NEGERI 6 SAMARINDA - Hasiholan, Raphael Dwiputra; Rusdiana, Rusdiana; Romisa, Fahmi (LPPM Universitas Bina Bangsa, 2025)
This research aims to develop Android-based interactive learning media for Informatics subjects in Grade VIII at SMP N 6 Samarinda, and to determine the feasibility of using Android-based interactive learning media as a learning tool for Informatics in Grade VIII at SMP N 6 Samarinda. This type of research applies the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). Data collection techniques used include observation, interviews, and questionnaires. The data analysis techniques applied were descriptive qualitative analysis and quantitative analysis. The research subjects involved were 1 subject matter expert, 3 media experts, and 24 eighth-grade students at SMP N 6 Samarinda, while the object studied was the feasibility of developing Android-based learning media for Grade VIII at SMP N 6 Samarinda. The research results obtained based on validation show that the material expert validation achieved a score of 4.7 in the “Highly Feasible” category, the validation by 3 media experts achieved a score of 4.6 in the “Highly Feasible” category, and the student trials achieved a score of 4.5 in the “Highly Feasible” category. From these results, it can be concluded that the learning media developed using PowerPoint is “Highly Feasible” to be used as a learning medium for Microsoft Word material.